Sales Consignment and Nasal Shedding of Equine Herpesvirus‐1 (EHV‐1) and 4 (EHV‐4) in Young Thoroughbred Horses in South Africa. (September 2014) - Badenhorst, M.; Page, P.C.; Ganswindt, A.; Guthrie, A.J.; Schulman, M.L.
Abstract : Reasons for performing study: Commingling of horses from various populations, together with stress associated with transport and confinement at a sales complex, may predispose horses to EHV‐1 and ‐4 shedding and transmission. Current information on the prevalence and associated risk factors of EHV‐1 and ‐4 in South Africa is limited. Relevant research could enhance scientific‐based risk management strategies for horses attending sales events. Objectives: Detect nasal shedding of EHV‐1 and ‐4 at a sales event. Identify the temporal pattern of viral shedding. Investigate the association between clinical signs and EHV‐1 and ‐4 shedding. Identify risk factors for EHV‐1 and ‐4 shedding and transmission. Study design: Prospective cohort study. Methods: Data was collected over a 9 day period during August 2013 at the National Two Year Old Sales in Germiston, South Africa. The study population included 90 Thoroughbreds (51 colts, 39 fillies) in their second year of life that originated from 8 studs situated in 3 provinces. Nasal swabs were collected from each horse on arrival and on departure from the event. During their stay horses were monitored twice daily for pyrexia and once daily for nasal discharge. Nasal swabs were collected daily from any horse with nasal discharge and/or pyrexia. Nasal swabs were submitted for qPCR to detect EHV‐1 and ‐4. Results: No EHV‐1 shedding was detected; however, 14.4% of the population shed EHV‐4. A biphasic shedding pattern with peaks one day post arrival and on the first day of auction was observed. Pyrexia, with or without nasal discharge, was observed prior to first shedding in 61.5% of EHV‐4‐positive horses. Province, associated longer travel duration and smaller resident horse populations on farms of origin were associated with increased risk of EHV‐4 shedding. Conclusions: Young Thoroughbreds consigned to a South African sale shed EHV‐4. Pyrexia proved useful to identify impending EHV‐4 shedding. Ethical animal research:  The study was approved by the Animal Ethics Committee (AEC) of the University of Pretoria (Study V040‐13). Informed, written consent for participation was obtained from the owners of each of the studs included in the study.Sources of funding:  Funding for this study was provided by Racing South Africa and the Departments of Companion Animal Clinical Studies and Production Animal Clinical Studies, Faculty of Veterinary Science, University of Pretoria.Competing interests:  None.